Annual Training Program in Radiological Protection in a Radiotherapy Service – A Case Study (Brazilian Journal of Radiation Sciences (BJRS), 2024)
The safety and radiological protection in radiotherapy services are essential to ensure the safe use of ionizing radiation for the benefit of patients and involved professionals. Evaluative research on multidisciplinary teams regarding annual training in radiological protection in radiotherapy is scarce. It is crucial to understand how professionals from each area assess the acquired knowledge and apply theoretical precepts in the radiotherapy service. This study aimed to analyze the annual radiological protection training offered in a radiotherapy service, and as specific objectives, to map the knowledge of professionals from each area regarding radiological protection applied during training. This is a qualitative research of the case study type. Data collection occurred through semi-structured interviews, simple observation, and documentary analysis, organized in the ATLAS.ti software version 24. The results indicate significant challenges, including the lack of understanding of basic principles by professionals, the absence of integration between the team and supervisors, and the lack of clear definition of the training format in current regulations. The results were categorized into: professionals' knowledge of radiological protection; training weaknesses; training strengths; suggestions for training delivery methods and topics in radiological protection. More effective educational strategies, along with precise guidance on the training format, emerge as promising solutions to overcome these challenges.